Formation of Tolerance in Students of Classical Higher Schools with Values of Physical Education - A A Budarnikov; A V Kozlov (Peoples' Friendship University of Russia (RUDN University), 2014)
The paper presents the current status and problems of physical education in the classical higher school, developing the idea of orienteering sports and recreation activities in higher school towards the formation of tolerance in students with the help of physical education.